Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1177/41.2.8419459
|View full text |Cite
|
Sign up to set email alerts
|

Localization of bone sialoprotein (BSP) to Golgi and post-Golgi secretory structures in osteoblasts and to discrete sites in early bone matrix.

Abstract: Bone sialoprotein (BSP), a bone matrix-enriched glycoprotein containing the Arg-Gly-Asp (RGD) motif and endowed with cell binding properties, was localized in osteoblasts and early bone matrix of developing rat bone at the ultrastructural level. Preliminary light microscopic observations indicated that intracellular labelling was restricted to a paranuclear dot corresponding to the "negative Golgi image" of classical histology. The same pattern was observed whether antisera against the fully glycosylated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 8 publications
(11 reference statements)
8
72
0
4
Order By: Relevance
“…Several other groups have reported the presence of discrete spherical or ovoid shaped entities at the mineralization front of bone having similar structural and elemental characteristics to what is described in the current study [11][12][13][14][15][16][17][18][19]32,33]. A unique contribution of the present study to this existing literature is the isolation and initial biochemical characterization of these mineralization front structures.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Several other groups have reported the presence of discrete spherical or ovoid shaped entities at the mineralization front of bone having similar structural and elemental characteristics to what is described in the current study [11][12][13][14][15][16][17][18][19]32,33]. A unique contribution of the present study to this existing literature is the isolation and initial biochemical characterization of these mineralization front structures.…”
Section: Discussionmentioning
confidence: 48%
“…Another finding from these tests revealed that calcospherulites incubated in type I collagen gels take on an ultrastructural appearance similar to that of crystal ghost aggregates observed in vivo [9]. Since both our isolated calcospherulites and crystal ghost aggregates [13] contain BSP, then this ultrastructural similarity may not be coincidental and might suggest a structure/function identity. Altogether, the similarities between our in vitro results and observations made from in vivo samples suggest that calcospherulites likely mediate the mineralization of osteoid at the mineralization front of bone tissue in vivo.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These were small needle-like crystals associated with fibrillar extracellular matrix deposits and intracellular spherical structures, with an X-ray diffraction pattern resembling human bone [15]. This pattern resembled the early stages in mineral formation in primary osteoblast cultures [2,4,9] and normal rat bone sections [3], and their chemical composition was bio-apatitic in nature, resembling normal bone in crystal size and calcium phosphate ratio [15]. Furthermore, when UMR cells were experimentally transplanted in animals they formed mineralized bone trabeculae at ectopic sites [I 11.…”
Section: Innhibition Of Chful and N?inerolixtion In Bsp Osteohlustsmentioning
confidence: 99%